(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
This research aims to measure the discrepancy between the accounting income which is prepared according to generally accepted accounting principles and the tax income that is being prepared according to the rules and tax laws, and find out the most important differences that arise between incomes.The research found the most important to the following conclusions:1.Faces determining the tax base for companies subject to income challenges related to the weakness of the efficiency and the possibility of technical angel tax and its ability to examine the financial statements submitted to the tax administration tax.2.That the tax system in Iraq does not comply with accepted accounting principles generally accepted.The research recommends the need to work to create a new legal ground help to reduce the disparity between the accounting and income tax revenue by making adjustments and reforms fast on the tax laws and regulations.